1977
DOI: 10.1107/s0567740877005640
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of cis-dichlorobis(cyclohexylamine)platinum(II)

Abstract: The structure of cis-dichlorobis(cyclohexylamine)plafinum (II)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The distortion found in cis-IPt(C6H~NH2)2C12] (Iball & Scrimgeour, 1977) is even greater. Both CI-Pt-CI and N--Pt--N angles are 151 ° and the PtC12-PtN 2 dihedral angle is 45 °.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The distortion found in cis-IPt(C6H~NH2)2C12] (Iball & Scrimgeour, 1977) is even greater. Both CI-Pt-CI and N--Pt--N angles are 151 ° and the PtC12-PtN 2 dihedral angle is 45 °.…”
Section: Discussionmentioning
confidence: 83%
“…An alternative reason for the lower toxicity of cis-[Pt(C6H~tNH2)2C12] might lie in the apparent distortion of the structure observed by Faggiani et al (1976) and Iball & Scrimgeour (1977), but detailed examination does not show this to be the case. have not yet solved this structure and have yet to be convinced that the distortion is not an artifact of a space-group error.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…We have made a number of unsuccessful attempts to synthesize suitable crystals of cis-dichlorobis(cyclohexylamine)platinum(II) for an X-ray structure determination, particularly since we have shown that the reported structure of this compound (Iball & Scrimgeour, 1977) is an incorrect solution of the structure of the corresponding trans isomer (Zanotti, Del Pra, Bombieri & Tamburro, 1978;Lock, Speranzini & Zvagulis, 1980). So far we have had no success, although we have examined the structure of the compound solvated with hexamethylphosphoramide (Lock et aL, 1980).…”
mentioning
confidence: 99%